I need to solve the differential equation $-x^2 y'' = \lambda y$ by transforming the differential equation to a equation with constant coefficients. I need to do this by using $f(x) = y(e^x)$. If I do this, I become the equation: $y''(e^x) + \frac{y'(e^x)}{e^x}+ \frac{\lambda y(e^x)}{(e^x)^2} = 0$

The I find a general solation of: $$y(e^x) = C \exp\left(\frac{-1+\sqrt{1- \frac{4\lambda}{x^2}}}{2(e^x)^2}\right) + C \exp\left(\frac{-1-\sqrt{1- \frac{4\lambda}{x^2}}}{2(e^x)^2}\right) $$

But Wolfram alpha gives the solution: $$y(x) = c x^{\frac{1}{2} + \frac{1}{2}*\sqrt{1-4\lambda}} + c x^{\frac{1}{2} - \frac{1}{2}*\sqrt{1-4\lambda}} $$

Can someone help me figure this out?


It is true that the given ODE can be transformed into an equation with constant coefficients by substituting $x:=e^t$. But the necessary computations are and not at all straightforward, hence error prone.

Consider your equation as a Eulerian ODE instead, and use the "Ansatz" $y(x):=x^\alpha$, with $\alpha\in{\mathbb C}$ to be determined. This leads to $$-x^2\cdot \alpha(\alpha-1)x^{\alpha-2}=\lambda x^{\alpha}\ ,$$ hence to the "characteristic equation" $$\alpha^2-\alpha+\lambda=0\ .$$ This equation has the two solutions ${1\over2}\bigl(1\pm\sqrt{1-4\lambda}\bigr)$ and leads to the following general solution of the given ODE: $$y(x)=C_1 x^{(1+\sqrt{1-4\lambda})/2}+C_2x^{(1-\sqrt{1-4\lambda})/2}\ .$$ If these are real, fine. Otherwise addditional measures (via complex exponentials) are necessary.

For the desired transformation define $$z(t):=y(e^t)$$ and compute, using the chain rule, $$\dot z(t)=y'(e^t)\>e^t,\qquad \ddot z(t)=y''(e^t)\>e^{2t}+y'(e^t)\>e^t=-\lambda z(t)+\dot z(t)\ .$$ It folows that $t\mapsto z(t)$ satisfies the constant coefficient equation $$\ddot z-\dot z+\lambda z=0\ .$$

  • $\begingroup$ This certainly is a good solution but the exercise really said it was preferable to use the transformation $f(x):= (e^x)$. How would it look like if you use this transformation or is it impossible? But this method seems to be easier by the way. $\endgroup$ – Belgium_Physics Dec 13 '17 at 15:00

It is true that using $f(X)=y(e^X)$ allows to transform the ODE into an ODE with constant coefficients, but with a little trick at first beginning :

$f(X)=y(e^X)$ is valid any symbol of variable, for example $f(t)=y(e^t)$

Let $e^t=x \quad\to\quad f(t)=y(x)$

$dx=e^tdt=xdt \quad\to\quad \frac{dt}{dx}=\frac{1}{x}$


$\frac{d^2y}{dx^2}=\frac{d\left(\frac{1}{x}\frac{df}{dt}\right)}{dx} = -\frac{1}{x^2}\frac{df}{dt}+\frac{1}{x}\frac{d^2f}{dt^2}\frac{dt}{dx}= -\frac{1}{x^2}\frac{df}{dt}+\frac{1}{x^2}\frac{d^2f}{dt^2}$

$-x^2\frac{d^2y}{dx^2}=\lambda y=x^2\left(-\frac{1}{x^2}\frac{df}{dt}+\frac{1}{x^2}\frac{d^2f}{dt^2}\right)= -\frac{df}{dt}+\frac{d^2f}{dt^2}$

$$\frac{d^2f}{dt^2}-\frac{df}{dt}-\lambda f(t)=0$$

This is a linear ODE with constant coefficients easy to solve. $$f(t)= c_1e^{\frac{1+\sqrt{4\lambda+1}}{2}t}+c_2e^{\frac{1-\sqrt{4\lambda+1}}{2}t}=c_1(e^t)^{\frac{1+\sqrt{4\lambda+1}}{2}}+c_2(e^t)^{\frac{1-\sqrt{4\lambda+1}}{2}} $$

$$y(x)=c_1 x^{\frac{1+\sqrt{4\lambda+1}}{2}}+c_2x^{\frac{1-\sqrt{4\lambda+1}}{2}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.